The Nandi Mandapa or the Vahana Mandapa - Temples of India Project Team (Jio Institute, 2024)
The Nandi mandapa (pillared hall), or the vahana mandapa, stands in front of the main entrance of the Suhaveshwar Temple. It has a flight of stairs to its east. It must have had four pillars supporting a shikhara (superstructure) at one point. This Nandi mandapa’s remains are similar to the one in front of the Mahanaleshwar Temple.